Familial platelet disorder due to germline exonic deletions in RUNX1: a diagnostic challenge with distinct alterations of the transcript isoform equilibrium. Issue 10 (24th August 2022) - Engvall, Marie; Karlsson, Ylva; Kuchinskaya, Ekaterina; Jörnegren, Åsa; Mathot, Lucy; Pandzic, Tatjana; Palle, Josefine; Ljungström, Viktor; Cavelier, Lucia; Hellström Lindberg, Eva; Cammenga, Jörg; Baliakas, Panagiotis
Abstract: Germline pathogenic variants in RUNX1 are associated with familial platelet disorder with predisposition to myeloid malignancies (FPD/MM) with intragenic deletions in RUNX1 accounting for almost 7% of all reported variants. We present two new pedigrees with FPD/MM carrying two different germline RUNX1 intragenic deletions. The aforementioned deletions encompass exons 1–2 and 9–10 respectively, with the exon 9–10 deletion being previously unreported. RNA sequencing of patients carrying the exon 9–10 deletion revealed a fusion with LINC00160 resulting in a change in the 3′ sequence of RUNX1 . Expression analysis of the transcript isoform demonstrated altered RUNX1a/b/c ratios in carriers from both families compared to controls. Our data provide evidence on the impact of intragenic RUNX1 deletions on transcript isoform expression and highlight the importance of routinely performing copy number variant analysis in patients with suspected MM with germline predisposition.